2016
DOI: 10.1152/jn.01001.2015
|View full text |Cite
|
Sign up to set email alerts
|

Odors enhance slow-wave activity in non-rapid eye movement sleep

Abstract: Most forms of suprathreshold sensory stimulation perturb sleep. In contrast, presentation of pure olfactory or mild trigeminal odorants does not lead to behavioral or physiological arousal. In fact, some odors promote objective and subjective measures of sleep quality in humans and rodents. The brain mechanisms underlying these sleep-protective properties of olfaction remain unclear. Slow oscillations in the electroencephalogram (EEG) are a marker of deep sleep, and K complexes (KCs) are an EEG marker of corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…The local TMR effects on cortical sleep oscillations extend previous studies showing that olfactory stimulation during sleep enhances SWA [23,44]. We found that SWA increase was lower in the cued hemisphere and negatively correlates with memory for cued items (but not for uncued items).…”
Section: Discussionsupporting
confidence: 87%
“…The local TMR effects on cortical sleep oscillations extend previous studies showing that olfactory stimulation during sleep enhances SWA [23,44]. We found that SWA increase was lower in the cued hemisphere and negatively correlates with memory for cued items (but not for uncued items).…”
Section: Discussionsupporting
confidence: 87%
“…Sleep plays a critical role in emotional regulation and memory consolidation (Yoo et al, 2007;Altena et al, 2016), and sleep is often impaired in normal and pathological ageing (Mander et al, 2017). Although odor detection is greatly reduced during NREM sleep in humans (Carskadon and Herz, 2004) and animal models (Barnes et al, 2011), odors presented during NREM sleep in humans modulate respiration (Arzi et al, 2010) and enhance NREM delta power (Perl et al, 2016), which could enhance sleep quality. Finally, sensory stimulation, including odor training, can improve sensory function in the elderly, which in turn can enhance cognitive functioning (Birte-Antina et al, 2018;Leon and Woo, 2018).…”
Section: Ageing and Dementiamentioning
confidence: 99%
“…Auditory stimulation uses tones to modify cortical activity. In principle, all senses, including vision, hearing, scent [26], and touch, can be used for sensory stimulation [6], yet in humans auditory stimulation appears to be particularly well suited to modulate sleep. More specifically, auditory stimulation is the most reliable way to induce single slow oscillations (K-complexes) in humans [27][28][29].…”
Section: Nibs For Modulation Of Arousal and Sleepmentioning
confidence: 99%